MONITORING OF ANTICONVULSANT DRUG SIDE EFFECTS IN OUTPATIENTS WITH EPILEPSY - Sari, Santi Purna; Salma S, Natasha Kurnia; Rianti, Alfina (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to monitor the side effects of carbamazepine, phenytoin, and valproic acid, and combinations of these drugs in adult patients with epilepsy, to raise awareness of the importance of drug side effect monitoring in hospitals. Methods: In this prospective study, descriptive data were collected from patients who met the inclusion criteria of complete samples. Primary data were obtained using questionnaires, secondary data were collected from medical records, and analyses were performed using the Naranjo algorithm. Results: Among the 54 included patients, 38 (70.37%) of them experienced drug side effects, and the most frequently observed side effect occurred in 48.15% of study subjects. Conclusion: No correlation was identified between side effects and age (p=0.903) or gender (p=1.000).